Ecological water quality of the Three Gorges Reservoir and its relationship with land covers in the reservoir area: implications for reservoir management - Ye, Lin; Chen, Kefeng; Cheng, Jingjing; Tan, Lu; Zhang, Min; Zhang, Xiaoguang; Cai, Qinghua (Frontiers in Environmental Science, 2023)
In this study, we evaluated the ecological water quality of the entire Three Gorges Reservoir (TGR) and further examined the relationship with changes in watershed land covers. Using the phytoplankton functional group-based Q index, we found that the ecological water quality in the mainstream (previously known as the Yangtze River) of TGR is good, with 84% of sites in the status above good. While the poor ecological water quality was generally observed in the backwater regions of TGR’s tributaries, with 79% of sites below the good status. Further investigating the potential impacts of the changes in land covers within the watershed on the tributary ecological water quality, we found that the percentage of urban and farmland areas had a significant (p < 0.05) negative correlation with the Q index-based ecological water quality of the tributary bays, and the forest cover had a marginally significant (p = 0.058) positive correlation with the ecological water quality. As a comparison, total nitrogen and total phosphorus in the tributary backwater regions of TGR had no reasonable correlation with the land covers within the watershed. Our study highlights that watershed management can enhance the ecological water quality in the backwater regions of TGR’s tributaries, but it likely to be a long-term process. This implies considerations of other rapid measures, such as the water level regulation approach, should also be considered in reservoir management. Our study underscores the importance of ecological water quality assessment in reservoir management and provides insights into the impacts of changes in watershed land covers on ecological water quality in backwater regions of TGR’s tributaries.